Pengaruh BI Rate, Exchange Rate(IDR/USD), Dan Inflasi Terhadap Indeks Saham Syariah Yang Tercatat Di JII Di Masa Pandemi Covid-19 Tahun 2020. - Majid, Abdul; Mardani, Ronny Malavia; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this research is to determine the influence of the Bi Rate, Exchange Rate (IDR/USD), and Inflation on the Sharia Stock Index listed on JII. In this research, the population used was 30 Sharia Stock Index companies registered with (JII) during the 2020 Covid-19 pandemic. The data used as samples were Sharia Stock Index data, annual BI Rate data, Exchange Rates and Inflation. All research variable data uses annual data, so data is obtained for the period January 2020 – December 2020. Bi Rate, Exchange Rate and Inflation on the Stock Index simultaneously influence the Sharia Stock Index recorded on JII for the 2020 period. Bi Rate has a negative and significant effect on Sharia Stock Index recorded on JII for the 2020 period. The exchange rate has a positive and significant influence on the Sharia Stock Index recorded on JII for the 2020 period. Inflation has a positive and insignificant effect on the Sharia Stock Index recorded on JII for the 2020 period. Keywords: BI RATE, EXCHANGE RATE, INFLASI, Trade Volume, Stock Price